Conversations with Pragmatism : A Multi-Disciplinary Study - Bube, Paul Custodio; Geller, Jeffery (BRILL, 2002)
This book represents the reflections of scholars coming from varied disciplinary backgrounds who have found a conversation partner in pragmatism. The "conversations" recorded here demonstrate pragmatism's versatility and contemporary relevance. Whether it be rhetoric, literature, philosophy, religion, or social psychology, pragmatism provides the contributors fruitful insights into and methods of examining both practical and theoretical issues.
Keywords: Pragmatism.; Pragmatisme.; pragmatism.; Pragmatism